Accommodating conscientious objection in the midwifery workforce: a ratio-data analysis of midwives, birth and late abortions in 18 European countries in 2016 - Valerie Fleming; Clare Maxwell; Beate Ramsayer (BMC, 2020)
Abstract Background In recent years, the role of a midwife has expanded to include the provision of abortion-related care. The laws on abortion in many European countries allow for those who hold a conscientious objection to participating to refrain from such participation. However, some writers have expressed concerns that this may have a detrimental effect on the workforce and limit women's access to the service. Method The aim of this study was to provide a picture of the potential exposure midwives in Europe have to late abortions, an important factor in the integration of accommodation of conscientious objection to abortion by midwives into workload planning. We collected data from Ministries of Health or government statistical departments in 32 European countries on numbers of births, abortions, late abortions and midwives in 2016. We conducted a ratio-data analysis in those countries that met the inclusion criteria. Results Eighteen of the 32 countries provided full data; thus, our calculations are based on a total of 4 036 633 live births, 49 834 late abortions and a total of 132 071 midwives. The calculated ratios of live births to midwife, abortions to midwife and late abortions to midwife illustrate the wide variations between countries in relation to ratios of midwives to live births (15.22-53.99) and late abortions (0.17-1.47) Conclusions This study provides the first comprehensive insight to ratios relating to birth and abortion, especially late abortion services, with regard to the midwifery workforce. It is essential to improve the reporting of abortion data and access to it within Europe to support evidence-informed decisions on optimising the contribution of the midwifery workforce especially within highly contentious fields such as abortion services. The study's findings suggest that there should be neither be any difficulty for those who are responsible for workload allocation nor compromises to a women's right to abortion services.